Dissection of two quantitative trait loci for grain length linked on the long arm of chromosome 5 in rice. Issue 6 (21st October 2021) - Niu, Xiaojun; Zhang, Zhenhua; Chan, Aye Nyein; Fan, Yeyang; Tang, Shaoqing; Yu, Sibin; Zhuang, Jieyun; Zhu, Yujun
Abstract: Grain size is the major determinant of grain weight and has an important role in grain quality. It is controlled by several major quantitative trait loci (QTL) and many minor QTL. Identification of QTL for grain size is important for understanding the genetic and molecular network regulating grain size in rice ( Oryza sativa L.). Following previous identification of QTL for grain weight and size using an F2:3 family derived from the indica rice cross Teqing/IRBB52, one QTL, qTGW5, having significant effects on grain length and weight, was targeted for validation, dissection, and fine‐mapping. First, the effect of qTGW5 was validated using two near‐isogenic line (NIL)‐F2 populations. Then, qTGW5 was dissected into two closely linked QTL using four NIL populations. One of them, qGL5.1, having significant effects on grain length, width, and weight, was located within an 1, 896.4‐kb region. The other one, qGL5.2, controlling grain length, was further delimited into a 68.8‐kb region using seven NIL‐F2 populations. Six annotated genes were found in the qGL5.2 region, of which five showed nucleotide polymorphisms between the two parental lines. Three of the six annotated genes showed significant expression differences between NIL Teqing and NIL IRBB52 in young panicles using quantitative real‐time polymerase chain reaction. The results will facilitate cloning the minor QTL and understanding the genetic architecture for grain size in rice. Core Ideas: Two minor QTL for grain length were newly identified and validated. The qGL5.2 was fine‐mapped within a 68.8‐kb region containing six annotated genes. Our findings provide good targets to further investigate the trade‐off between grain number and size.